Reformulation of Mafqud Husband Regulations in the Indonesian Marriage Law System in the Perspective of Maslahah Al Buthi - Miftakur Rohman; Tutik Hamidah; Khoirul Hidayah (Universitas Nurul Jadid, 2025)
One of the issues that often arises in the context of marriage is the case of